In vitro Targetability Validation of Peptide-Functionalized Mesoporous Silica Nanoparticles in the Presence of Serum Proteins - Paramonov, Valeriy M.; Gerstenberg, Melanie; Sahlgren, Cecilia; Lindén, Mika; Rivero-Müller, Adolfo (Frontiers in Chemistry, 2020)
Demonstration of receptor-mediated targeting of nanoparticles to specific organs and/or cell types is an integral aim in many bionanomedicine development projects. However, engagement of targeted receptors with ligands on nanocarriers, which is the cornerstone of the active targeting concept, is challenging to study under biologically relevant conditions and thus often stays overlooked. In this work, we utilize in-house established bioassay for in vitro targetability validation of mesoporous silica nanoparticles (MSNs), functionalized with high-affinity peptide ligands to somatostatin receptors via protective group chemistry, ensuring correct orientation of the peptide’s pharmacophore. We demonstrate that targeted nanoparticles, but not scrambled peptide - decorated counterparts, specifically engage the targeted receptors in living cells in culture media containing serum protein. The importance of being able to exclude false positives originating from premature detachment of targeting peptides from the MSNs is highlighted.